2022
DOI: 10.2174/1871526522666220509054535
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of Adenovirus Genotypes 40 and 41 in Children with Acute Gastroenteritis

Abstract: Background: Adenovirus is a common virus associated with acute gastroenteritis in children. There are certain genotypes that are prevalent in these infections such as genotypes 40 and 41. Objective: The aim of the present study was to investigate the incidence of adenovirus genotypes 40 and 41 in children with acute gastroenteritis by polymerase chain reaction (PCR) and also to determine the possibility of Adenovirus co-infections with Rota virus. Method: The study was cross- sectional study that included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Three different studies reported different ratios of children testing positive for adenovirus, including 5/13, 40/53, and 9/9 [Table 3]. [2,4,6] The age of the patients with severe acute hepatitis of unknown etiology is consistent with that previously reported for adenovirus-infected children [7] . Furthermore, the adenovirus DNA levels in those who had underwent liver transplantation were approximately 12-fold higher than the adenovirus DNA levels in those who had not [5] .…”
Section: Potential Etiologysupporting
confidence: 73%
See 1 more Smart Citation
“…Three different studies reported different ratios of children testing positive for adenovirus, including 5/13, 40/53, and 9/9 [Table 3]. [2,4,6] The age of the patients with severe acute hepatitis of unknown etiology is consistent with that previously reported for adenovirus-infected children [7] . Furthermore, the adenovirus DNA levels in those who had underwent liver transplantation were approximately 12-fold higher than the adenovirus DNA levels in those who had not [5] .…”
Section: Potential Etiologysupporting
confidence: 73%
“…[ 2 , 4 , 6 ] The age of the patients with severe acute hepatitis of unknown etiology is consistent with that previously reported for adenovirus-infected children. [ 7 ] Furthermore, the adenovirus DNA levels in those who had underwent liver transplantation were approximately 12-fold higher than the adenovirus DNA levels in those who had not. [ 5 ] A preliminary study identified the virus causing the infection as adenovirus type 41F via molecular testing, but this was performed without full genome sequencing.…”
Section: Potential Etiologymentioning
confidence: 99%
“… 1 , 4 , 5 Furthermore, the two cohorts of children (severe acute hepatitis of unknown origin or adenovirus infection) had a similar age range. 6 In addition, the England-based patients who received liver transplantation had approximately 12-fold adenovirus DNA levels than those who did not receive liver transplantation. 7 However, more robust data are still needed to support this notion.…”
Section: Disease Etiology: Induced By Pathogens or Non-infectious Fac...mentioning
confidence: 99%
“…The most common symptoms include fever, cough, rhinorrhea, and diarrhea [10,11]. Notably, certain serotypes of HAdV were found to be associated with different diseases and symptoms [12][13][14]. HAdV is responsible for multiple outbreaks all over the world [15][16][17].…”
mentioning
confidence: 99%